Spline solutions for nonlinear two point boundary value problems - Riaz A. Usmani (International Journal of Mathematics and Mathematical Sciences)
Necessary formulas are developed for obtaining cubic, quartic, quintic, and sextic spline solutions of nonlinear boundary value problems. These methods enable us to approximate the solution of the boundary value problems, as well as their successive derivatives smoothly. Numerical evidence is included to demonstrate the relative performance of these four techniques.